2001
DOI: 10.1016/s0014-5793(01)02233-5
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferricin B causes depolarization of the cytoplasmic membrane of Escherichia coli ATCC 25922 and fusion of negatively charged liposomes

Abstract: Antimicrobial peptides have been extensively studied in order to elucidate their mode of action. Most of these peptides have been shown to exert a bactericidal effect on the cytoplasmic membrane of bacteria. Lactoferricin is an antimicrobial peptide with a net positive charge and an amphipatic structure. In this study we examine the effect of bovine lactoferricin (lactoferricin B; Lfcin B) on bacterial membranes. We show that Lfcin B neither lyses bacteria, nor causes a major leakage from liposomes. Lfcin B de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 22 publications
(21 reference statements)
4
62
0
1
Order By: Relevance
“…The disulfide cross linked, antimicrobial β-hairpin peptide lactoferricin retains its antimicrobial biological activity even after 19 of its 25 residues, including all of the disulfide cross links are removed, requiring only a core linear hexapeptide that is as active as the 25-residue disulfide-cross linked parent β-hairpin (55). In fact many derivatives of lactoferricin are highly active antimicrobial peptides (56)(57)(58). Disulfide cross linked variants of our FSKRGY have antimicrobial activity that is indistinguishable from the non-cross linked peptide (JRM and WCW, unpublished observations).…”
Section: Correlation Between Structure and Function In Membranesmentioning
confidence: 99%
“…The disulfide cross linked, antimicrobial β-hairpin peptide lactoferricin retains its antimicrobial biological activity even after 19 of its 25 residues, including all of the disulfide cross links are removed, requiring only a core linear hexapeptide that is as active as the 25-residue disulfide-cross linked parent β-hairpin (55). In fact many derivatives of lactoferricin are highly active antimicrobial peptides (56)(57)(58). Disulfide cross linked variants of our FSKRGY have antimicrobial activity that is indistinguishable from the non-cross linked peptide (JRM and WCW, unpublished observations).…”
Section: Correlation Between Structure and Function In Membranesmentioning
confidence: 99%
“…The bactericidal effect of many CAPs is thought to be due to the action on the cytoplasmic membrane of the susceptible bacteria, possibly through the formation of pores or destabilization of the membrane bilayer structure leading to lysis of the cell [4,5]. Some CAPs such as buforin 11 [6], indolicidin [7], apidaecin [8], PR 39 [9], PR 26 [10], bactenecin [11] and lactoferricin B [12,13] have been reported to have intracellular targets. In a recent review article, Wimley [14] pointed out that many antimicrobial peptides do not porate or damage bacterial membranes but rather produce transient pores as demonstrated by using unilamellar liposomes loaded with probes.…”
Section: Introductionmentioning
confidence: 99%
“…Some AMPs have been proven to penetrate the cell membrane and affect the intracellular targets within the cells (11)(12)(13); Lfcin B is one of these AMPs (14 -18). Some studies have indicated that Lfcin B leads to the depolarization of the cell membrane and does not lyse the cells (19); Lfcin B has been shown to inhibit the macromolecular synthesis of cells, which suggests that the intracellular targets of Lfcin B may exist (12,19,20).…”
mentioning
confidence: 99%